2009
DOI: 10.12927/hcpol.2009.20806
|View full text |Cite
|
Sign up to set email alerts
|

Sorry, You Can't Have That Information: Data Holder Confusion Regarding Privacy Requirements for Personal Health Information and the Potential Chilling Effect on Health Research

Abstract: This study, conducted in Newfoundland and Labrador, assessed the level of awareness, perceptions and concerns of healthcare providers, health researchers, data managers and the general public about the collection, use and disclosure of personal health information (PHI) for research purposes. Data collection involved surveys and followup focus groups with participants. Results indicate a poor understanding generally with regard to privacy rights and responsibilities. Many professionals are unfamiliar with the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…The majority of patients were in favor of data sharing among researchers, especially within the field of AD research, although support for the sharing of personal information decreased with a higher risk of re-identifying the data [47][48][49][50][51][52][53][54]. Trinidad and colleagues [55] also found that both current and prospective research participants are generally supportive of the sharing of non-identifiable data among researchers.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of patients were in favor of data sharing among researchers, especially within the field of AD research, although support for the sharing of personal information decreased with a higher risk of re-identifying the data [47][48][49][50][51][52][53][54]. Trinidad and colleagues [55] also found that both current and prospective research participants are generally supportive of the sharing of non-identifiable data among researchers.…”
Section: Discussionmentioning
confidence: 99%
“…Also, historically, human research studies in this region have not been properly identified as such, but rather considered "quality improvement initiatives," which are not subject to similar privacy and confidentiality regulations. The Institute of Medicine in the USA clearly states that "an activity should be considered research rather than quality assessment or improvement if it explores previously unknown phenomena; collects data beyond those routinely collected for patient care; compares alternative treatments, interventions, or processes; manipulates a current process; and the results are expected to be published for general societal benefit (Pullman et al, 2009 Abu Dhabi government to encourage medical research, including research conducted by medical trainees, has enabled a thought shift from quality initiatives to human research, with emphasis on subject privacy and data confidentiality .…”
Section: Concept Familiaritymentioning
confidence: 99%
“…Such issues have been raised in the United States, 15,16 and we have contributed to the discussion in Canada. 17 Health information privacy legislation is pending in our province, and it provides for some flexibility with regard to the management of genetic information. 18 The familial nature of genetic information presents special challenges in this regard, which are beyond the scope of the present discussion.…”
Section: Lesson 5: the Need For An Effective And Efficient Means By Wmentioning
confidence: 99%